The Revolution of The Merit System Through Computer-Assisted Testing in The Recruitment of Village Officials in Kendal Regency - Murwantoro Murwantoro; Suparno Suparno; Karmanis Karmanis (Discourse Journal on Law and Society, 2026)
Bureaucratic reform at the village level is a crucial prerequisite for achieving professional, effective, and accountable village governance. One of the key pillars of this reform is the implementation of a merit system in the management of village human resources, particularly in the recruitment and appointment of village officials. In this context, the Computer-Assisted Test (CAT) has emerged as a policy innovation designed to enhance objectivity, transparency, and procedural fairness in the selection of village officials. This study aims to analyse the contribution of CAT implementation to strengthening the merit system and its impact on transforming village social conditions, especially in building public trust in village government. Quantitative data were collected through a survey of village residents and analysed using descriptive statistics, correlation analysis, and multiple linear regression in SPSS. Qualitative data were obtained through in-depth interviews, field observations, and document analysis to elaborate further and explain the quantitative findings. The results indicate that transparency, objectivity, and procedural fairness in the selection process have positive and significant effects on public trust in village government, with procedural fairness emerging as the most influential variable. Qualitative findings confirm that public acceptance of selection outcomes is more strongly influenced by perceptions of fairness and openness in the process than by the selection results themselves. This study concludes that the implementation of CAT functions not only serves as a technical selection instrument but also as an institutional mechanism that helps transform village social relations from patronage-based practices toward merit-based village governance.